The Effect Of Giving Young Coconut Water On Changes In Blood Pressure In Elderly People With Hypertension In The Wori Health Center Work Area, North Minahasa Regency - Agust A. Laya; Bayu Dwisetyo (Sean Institute, 2023)
Hypertension is a disease in which blood pressure will increase according to age. The treatment of hypertension can be pharmacologically and nonpharmacologically. Among them use young coconut water. The purpose of this research is to determine the effect of young coconut water to reduce the blood pressure of the elderly people with hypertension in the Wori Minahasa Utara Health Center Work Area. Using the pre-experiment method , with a one-group pre- and post-test design. The sample used was 18 people with accidental sampling. The data is collected using observation sheets and SOPs. Then it is processed using the SPSS program version 16.0 with a paired t-test. The results of this research were obtained by most respondents there were changes after being given young coconut water. The conclusion of the paired T test analysis results obtained the average blood pressure value before giving young coconut water, which was 139.00 with a P value (0.000) or <α (0.05) and after being given young coconut water, the average was 130.93 with a P value (0.000) or <α (0.05). process activities about stress management to reduce nurse stress